If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 + 2 + x(x) = 38 Multiply x * x 0 + 2 + x2 = 38 Combine like terms: 0 + 2 = 2 2 + x2 = 38 Solving 2 + x2 = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x2 = 38 + -2 Combine like terms: 2 + -2 = 0 0 + x2 = 38 + -2 x2 = 38 + -2 Combine like terms: 38 + -2 = 36 x2 = 36 Simplifying x2 = 36 Take the square root of each side: x = {-6, 6}
| 9(1.35)-2y=13 | | 7m^2+46m=-24 | | N-2.7=5.6 | | 3(-r-1)=4 | | z^2-14x=-40 | | 30=a+(2a+3)+(a+7) | | 3(2x+5)=4x+9 | | (24x-2)=(25x-8) | | 3(2x+5)=4x+8 | | 8x^2+13=213 | | X^4=.25 | | 140-x+40=180 | | 4(s+1.6)=-3s-1.2 | | 2(m-1)=3 | | 9a^2-6a+24=0 | | -3(4x-5)=-10 | | 80=10x+(x-1) | | 5xc=570 | | X+x*3= | | 7a-3=3A | | -23/-17 | | 197+2h=977 | | 2x+6x-9+4=3x-9+3 | | (5x-1)=(3x+1) | | -2a=3-a | | 5-x/38 | | 4(x^2+21x-280)=0 | | 10y^2+32y=0 | | -16x^2+32x-48=0 | | 10x-5/3=6x-5/2 | | 2x+6x-8+4=3x-9+3 | | (x-3)(x+4)=-30 |